Gabapentinoid and Opioid Utilization and Cost Trends Among Injured Workers. Issue 2 (February 2021) - Liu, Che; Lavin, Robert A.; Yuspeh, Larry; Leung, Nina; Kalia, Nimisha; Tsourmas, Nicholas F.; Williams, Leila; Bernacki, Edward J.; Tao, Xuguang (Grant)
Abstract : Objective: To characterize changes in opioid, gabapentin, and pregabalin utilization patterns and cost trends between 2008 and 2018 in a Louisiana workers' compensation claims population and explore the role of gabapentinoids as alternative analgesics during the opioid epidemic. Method: Filled prescriptions for gabapentinoids and opioids were studied for 11 years in a cohort of 18, 737 claimants. Results: The proportion of claimants prescribed gabapentin increased 2-fold (8.9% to 18.9%) and average drug cost per claimant decreased 22% ($612 to $480). The proportion of claimants prescribed pregabalin decreased approximately 80% (11.7% to 2.5%) and average drug cost per claim increased 224% ($911 to $2952). Proportion of claimants prescribed opioids decreased 20% (80% to 64.2%) and average drug cost per claim decreased 46% ($691 to $371). Conclusions: Utilization increased substantially for gabapentin and decreased for pregabalin and opioids.